Effects of low pH conditions on decay of methanogenic biomass. (15th July 2020) - Sun, Meng; Liu, Bing; Yanagawa, Katsunori; Ha, Nguyen Thi; Goel, Rajeev; Terashima, Mitsuharu; Yasui, Hidenari
Abstract: Acidic failure is relatively common in anaerobic digesters that receive readily biodegradable food wastes at high loading. Under low pH conditions, the activity of methanogenic biomass decreases resulting in complete failure of the digestion process. In this experimental study, we demonstrated that one of the causes for the digester failure under low pH conditions is due to accelerated decay of methanogenic biomass. When enriched acetate degrading methanogens were exposed to a low pH environment (pH = 5.1 with phosphoric acid) in a batch experiment without external substrate, the specific decay rate was observed to increase as much as 10 times of that at pH 7.0. The specific decay rate for formate degrader was also found to increase under low pH conditions whilst the fermentative microorganisms in the cultures appeared to be tolerant to low pH conditions. A Propidium Mono-Azide-quantitative Polymerase Chain Reaction (PMA-qPCR) analysis revealed that the archaeal biomass dominated by methanogens dropped by 71–79% from the initial concentration after 6 days of the acidic batch experiment whilst the bacterial biomass dominating acidogens decreased by only 25%. The decrease in the number of living cells in the batch experiments at different pH was monitored with time to determine a correlation between decay rate and incubation pH. Graphical abstract: Image 1 Highlights: The decay rate of methanogenic archaeal biomass was increased in low pH condition. Fluorescent staining method and PMA-qPCR could detect active biomass in sludge. The process recovery lag after acidic failure was modelled with the enhanced decay.